A new methodology to evaluate natural regeneration: A case study of Quercus ilex in the montado in Portugal - Gouveia-Barrocas, Eva; Gonçalves, Ana Cristina (Frontiers in Forests and Global Change, 2023)
Regeneration and recruitment are primordial for stand sustainability. However, natural regeneration is usually only evaluated by density and height, no details are provided regarding the saplings/seedlings traits. Hence, these regeneration studies are of limited selection power in a future silviculture management. The main goal of this study was to develop a new methodology that enables the evaluation of individual quality traits of regeneration in the early stages of stand development so that their future potential development can be assessed. Natural regeneration (NR) was evaluated using the conjugation of two methods: first using the Natural Regeneration Density (NRD) method; second using the new Natural Regeneration Tree Classification (NRTC). The NRTC is composed by a set of criteria, with categorical variables, that permits to evaluate the traits of the individuals and their potential for future recruitment. In this classification system five criteria were used, namely, upper storey influence to evaluate the competition of the trees of the upper storey cast on the regeneration individuals; crown isolation to characterize competition between seedlings/saplings; height as a surrogate of sapling development; diameter as a proxy of growth and tree habit as a proxy of the habit of saplings. To test both methods, we applied them in a case study of Quercus ilex in the montado agroforestry system in Portugal. Our results indicated that in 85% of the plots with a crown cover higher than 30%, we could find good quality natural regeneration oak saplings suited to be recruited and located outside of the upper storey crown projection. Only 15% of the plots with a crown cover higher than 30% were dominated by Cystus ladanifer and had almost no oak saplings. In the future, we suggest that the NRTC is used in all NR individuals in the forest inventory when the NR density is less than 200 NR individuals ha-1. The methodology developed needs further testing but our results indicate that it can be applied to other forest species in agroforestry systems or in other forest systems. This investigation highlighted a positive overview on the resilience of natural regeneration and Quercus ilex ecosystems in the Mediterranean.